O bem-estar subjetivo e a prática de exercício físico nos idosos: Um estudo com dois tipos de treino - Camila Paula Rocha Carneiro (2017)
The purpose of this dissertation was to study the aspects that encompass the aging process in today's society, specifically subjective well-being (BES), based on two different types of training. The present study aimed to analyze the benefits in BES in the elderly due to two different types of training (Bodybuilding and maintenance). Thirty-six elderly men and women (69% female and 31% male), aged 66-82 years (74.06 ± 4.68) participated in this study.A questionnaire was used, which was translated and adapted from three American questionnaires, namely: Satisfaction With Life Scale (SWLSp), Subjective Happiness Scale (SHSp) and Positive and Negative Affect Schedule (PANASp), by Watson, Clark and Tellegen (1988) ) Completed by students from two different classes in order to obtain personal information as well as the psychological situation in which each one was about the practice of physical activity.This questionnaire was applied in three different moments. Analysis of the results showed that both activities increased BES from the first to the second moment and from this to the third moment. None of the training modalities was the reason for the increase in BES, with AF practice being the largest source of benefits.